Skin-touch-actuated textile-based triboelectric nanogenerator with black phosphorous for durable biomechanical energy harvesting - Xiong, Jiaqing; Cui, Peng; Chen, Xiaoliang; Wang, Jiangxin; Parida, Kaushik; Lin, Meng-Fang; Lee, Pooi See (Nature Publishing Group, 2018)
Textiles that are capable of harvesting biomechanical energy via triboelectric effects are of interest for self-powered wearable electronics. Fabrication of conformable and durable textiles with high triboelectric outputs remains challenging. Here we propose a washable skin-touch-actuated textile-based triboelectric nanogenerator for harvesting mechanical energy from both voluntary and involuntary body motions. Black phosphorus encapsulated with hydrophobic cellulose oleoyl ester nanoparticles serves as a synergetic electron-trapping coating, rendering a textile nanogenerator with long-term reliability and high triboelectricity regardless of various extreme deformations, severe washing, and extended environmental exposure. Considerably high output (~250–880 V, ~0.48–1.1 µA cm−2) can be attained upon touching by hand with a small force (~5 N) and low frequency (~4 Hz), which can power light-emitting diodes and a digital watch. This conformable all-textile-nanogenerator is incorporable onto cloths/skin to capture the low output of 60 V from subtle involuntary friction with skin, well suited for users’ motion or daily operations.